A, PEMBERDAYAAN MASYARAKAT BERBASIS EDUKASI PERSEMAIAN TANAMAN DALAM MEWUJUDKAN KETAHANAN EKONOMI LOKAL DI KABUPATEN SORONG : COMMUNITY EMPOWERMENT BASED ON PLANT NURSERY EDUCATION TO ACHIEVE LOCAL ECONOMIC RESILIENCE IN SORONG REGENCY - Irnawati; Nur Hidaya; Muh. Fadli Hasa (LPPM Universitas Abdurrab, 2025)
This community service activity was carried out by lecturers and students from various departments and faculties of the University of Muhammadiyah Sorong through the Mahasiswa Berdampak program, focusing on education and community empowerment in the Aimas area, Sorong Regency, from September to October 2025. The aim of this activity was to improve the knowledge and skills of farmer groups in developing forest plant nurseries and Multi-Purpose Tree Species (MPTS) as an effort to support local economic resilience. The implementation methods included socialization, technical training on seedling media preparation, selection of superior seeds, seedling maintenance, and mentoring in managing community-based nurseries. This activity also encouraged active community participation in creating productive seed sources that can be utilized for both reforestation and income generation. The results showed an increased understanding among farmer groups regarding proper nursery techniques, as well as the emergence of community initiatives to independently develop nursery businesses. Thus, this program provided not only ecological benefits through the supply of plant seedlings but also sustainable economic benefits for the local community. It is expected that this activity will serve as a collaborative model of community service among students, lecturers, and local residents in supporting forestry development based on community economic empowerment in Sorong Regency.